Effects of mixed bacterial consortium on bioremediation of crude petroleum contaminated river sediments / Cindy Tan Soo Yun … [et al.] - Tan Soo Yun, Cindy; Ang, Chung Huap (2011)
Petroleum exploration refining and related activities around Lutong River,Miri Sarawak have caused deterioration to the river quality and sediments around the area. The crude petroleum is a mixture of mostly alkanes, cycloalkanes and various aromatic hydrocarbons with some organic compounds that contain nitrogen, oxygen and sulphur and traces of metals. Bioremediation can be defined as the use of living organisms to remove environmental pollutants from soil, water and gases. It is a natural process which is safe with minimal exposure risks. In the bioremediation process, the waste is detoxified and mineralised where the waste materials are converted into inorganic compounds such as carbon dioxide, water and methane. Since biological processes are usually specific, the growth conditions of microorganisms in a biodegradation process must be maintained in optimum conditions throughout the treatment to ensure successful removal of pollutants. Controlling the microbial populations by providing suitable environmental growth conditions as well as appropriate type and level of nutrients is challenging and may be difficult as the conditions may vary from site to site, especially in an ex-situ treatment.